Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Matematika Kelas V SDN 3 Bangkleyan Blora - Khusnul Estining Tyas; Aries Tika Damayani; Intan Rahmawati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The purpose of this study is to determine whether there is an effect of the Problem Based Learning model on the learning outcomes of class V grade mathematics at SD Negeri 3 Bangkleyan Blora. This study used a quantitative approach with a quasi-experimental research design. Data collection techniques in this research are observation, interviews, tests and documentation. Based on the results of the data processing carried out, the value of the T test was obtained the sig value was 0,000 and the calculated t value was 4,318. The value of sig ˂ 0,05 or 0,000 ˂ 0,05. The value of t arithmetic ˃ t table or 4,318 ˃ 2,010. Based on the t test, H0 is rejected and Ha is accepted, it can be concluded that there is a significant influence between the Problem Based Learning model on mathematics learning outcomes.